Biomaterial scaffolds in maxillofacial bone tissue engineering: A review of recent advances - Xiangya Huang; Yaxin Lou; Yihong Duan; He Liu; Jun Tian; Ya Shen; Xi Wei (Bioactive Materials, 2024)
Maxillofacial bone defects caused by congenital malformations, trauma, tumors, and inflammation can severely affect functions and aesthetics of maxillofacial region. Despite certain successful clinical applications of biomaterial scaffolds, ideal bone regeneration remains a challenge in maxillofacial region due to its irregular shape, complex structure, and unique biological functions. Scaffolds that address multiple needs of maxillofacial bone regeneration are under development to optimize bone regeneration capacity, costs, operational convenience. etc. In this review, we first highlight the special considerations of bone regeneration in maxillofacial region and provide an overview of the biomaterial scaffolds for maxillofacial bone regeneration under clinical examination and their efficacy, which provide basis and directions for future scaffold design. Latest advances of these scaffolds are then discussed, as well as future perspectives and challenges. Deepening our understanding of these scaffolds will help foster better innovations to improve the outcome of maxillofacial bone tissue engineering.